SNP genotyping results from Intertek Sweden outsourcing service - Raatz, Bodo (International Center for Tropical Agriculture, 2020)
Leaf discs were collected in the field and greenhouse and sent to Intertek Sweden for DNA extraction and SNP genotyping. 10 SNPs were evaluated on each sample. Data was used by the breeding program to select lines with favorable alleles.